Modeling argumentation with labeled deduction: formalization and theoretical considerations - Chesñevar, Carlos Iván (2001)
In the last years there has been an increasing demand of a variety of logical systems, prompted mostly by applications of logic in AI, logic programming and other related areas. Labeled Deductive Systems (LDS) were developed as a °exible methodology to formalize such a kind of complex logical systems. During the last decade defeasible argumentation has proven to be a con°uence point for many approaches to formalizing commonsense reasoning. Di®erent formalisms have been developed, many of them sharing common features. This paper summarizes the most relevant features of LDSar, a logical framework for defeasible argumentation based on LDS. We present a syntactic characterization of the framework, and discuss some emerging properties. We also show how di®erent existing argumentation frameworks are subsumed in LDSar